разложить многочлены на множетели

x3-12+6x2-2x

2x-3+xy2-2x-2-y3

6a3-21a2b+2ab2-7b3

2

Ответы и объяснения

2013-09-12T17:38:14+00:00
X3-12+6x2-2x=(-2x-12)+(6x^2+x^3)=-2(x+6)+x^2(6+x)=(6+x)(x^2-2)
2x-3+xy2-2x-2-y3=xy^2-5-y^3=y^2(x-y)-5 (в этом уравнении проверь условия, тут чего-то не хватает)
6a3-21a2b+2ab2-7b3=(-21a^2b-7b^3)+(6a^3+2ab^2)=-7b(3a^2+b^2)+2a(3a^2+b^2)= (3a^2+b^2)(2a-7b)
2013-09-12T17:56:41+00:00
6a3-21a2b+2ab2-7b3=(-21a^2b-7b^3)+(6a^3+2ab^2)=-7b(3a^2+b^2)+2a(3a^2+b^2)= (3a^2+b^2)(2a-7b)